Physiological Sympathetic Activation Reduces Systemic Inflammation: Role of Baroreflex and Chemoreflex - Brognara, Fernanda; Castania, Jaci Airton; Kanashiro, Alexandre; Dias, Daniel Penteado Martins; Salgado, Helio Cesar (Frontiers in Immunology, 2021)
Baroreflex and chemoreflex act through the autonomic nervous system, which is involved with the neural regulation of inflammation. The present study reports the effects of reflex physiological sympathetic activation in endotoxemic rats using bilateral carotid occlusion (BCO), a physiological approach involving the baroreflex and chemoreflex mechanisms and the influence of the baroreceptors and peripheral chemoreceptors, in the cardiovascular and systemic inflammatory responses. After lipopolysaccharide (LPS) administration, the arterial pressure was recorded under 360 min, in unanesthetized rats, and serial blood samples were collected to analyze the plasma cytokines levels. BCO elicited the reflex activation of the sympathetic nervous system, providing the following outcomes: (I) increased the power of the low-frequency band in the spectrum of the systolic arterial pressure during the BCO period; (II) reduced the levels of pro-inflammatory cytokines in plasma, including the tumor necrosis factor (TNF) and the interleukin (IL)-1β; (III) increased the plasma levels of anti-inflammatory cytokine IL-10, 90 min after LPS administration. Moreover, selective baroreceptor or chemoreceptor denervation deactivated mechanosensitive and chemical sensors, respectively, and decreased the release of the LPS-induced cytokine, but did not alter the BCO modulatory effects. These results show, for the first time, that physiological reflex activation of the sympathetic circuit decreases the inflammatory response in endotoxemic rats and suggest a novel function for the baroreceptors as immunosensors during the systemic inflammation.